Simultaneous determination and validation of emtricitabine, rilpivirine and tenofovir from biological samples using LC and CE methods. (9th January 2018) - Gumustas, Mehmet; Caglayan, Mehmet Gokhan; Onur, Feyyaz; Ozkan, Sibel A.
Abstract: A combination of antiretroviral agents is frequently used in effective treatment of the human immunodeficiency virus infection. In this study, two different separation methods are presented for the simultaneous determination of emtricitabine, rilpivirine and tenofovir from raw materials and urine samples. Developed liquid chromatography and capillary electrophoresis methods were thoroughly optimized for high analytical performances. Optimization of multiple variables at the same time by performing a minimum number of experiments was achieved by the Box–Behnken design, which is an experimental design in response surface methodology, in capillary electrophoresis. The results of the experimental design ensure minimum analysis time with well‐separated analytes. Separation conditions, such as different stationary phases, pH level, organic modifiers and temperatures in liquid chromatography method, were also optimized. In particular, among stationary phases, the core–shell column especially enhanced the effectiveness of separation in liquid chromatography. Both methods were fully validated and applied to real samples. The main advantage of the developed methods is the separation of the drug combination in a short time with high efficiency and without any time‐consuming steps.